Comparison of a Novel Weightbearing Cone Beam Computed Tomography Scanner Versus a Conventional Computed Tomography Scanner for Measuring Patellar Instability - Marzo, John; Kluczynski, Melissa; Notino, Anthony; Bisson, Leslie (Orthopaedic journal of sports medicine, 2016)
Background: Conventional computed tomography (CT) images are routinely used for diagnosing patellofemoral instability and are obtained with the patient in a supine position, nonweightbearing, with the knee in full extension, and with leg muscles relaxed. A new portable extremity cone beam CT (CBCT) scanner has been developed that may allow for more accurate diagnosis, as imaging can be performed with the patient standing, the knee flexed, and with leg muscles active. Purpose/Hypothesis: The purpose of this study was to compare CT measurements of patellar alignment on a prototype scanner versus conventional scanner in patients with known patellar instability. The hypothesis was that the measurements obtained with the knee flexed and the patient weightbearing would be less than those obtained from the conventional CT scan. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Twenty patients with a diagnosis of lateral patellar instability were imaged on both a conventional CT scanner and on a prototype CBCT scanner. Objective measures of patellofemoral alignment (tilt angle, congruence angle, tibial tuberosity–trochlear groove [TT-TG] offset) were assessed on images obtained from the prototype and conventional CT scans by 2 independent reviewers. Paired t tests were calculated to compare the mean measurement of patellofemoral alignment obtained from the prototype versus conventional CT. Interrater reliability was assessed using a 2-way mixed-effects model intraclass correlation coefficient (ICC) for tilt angle, congruence angle, and TT-TG offset on the prototype and conventional CT scans. Results: Measurements of patellofemoral alignment were significantly less when acquired by the new prototype CBCT scanner while subjects were weightbearing on a flexed knee. On the images from the prototype CBCT scan, the tilt angle averaged 18.2° ± 11.6° compared with 28.1° ± 7.1° on the conventional CT scan (P < .0001). The congruence angle was 3.0° ± 30.1° compared with 26.7° ± 18.1° on the conventional CT scan (P = .0002). Finally, the TT-TG offset distance averaged 12.3 ± 6.3 mm when measured on the CBCT scan compared with 20.1 ± 4.2 mm on the conventional CT scan (P < .0001). Good interrater reliability was found for tilt angle, congruence angle, and TT-TG offset on conventional and CBCT scans (ICC range, 0.79-0.96). Conclusion: In patients with patellar instability, measurements of patellofemoral alignment are reduced on images obtained from a new weightbearing extremity CBCT scanner on a flexed knee versus conventional CT in the supine position with a fully extended knee. Improvement in objective measurements of patellar alignment should lead to improved clinical and surgical care of patients with this condition.